ONTYCZNOŚĆ NARODU W MYŚLI CYPRIANA NORWIDA - Woźniewska-Działak, Magdalena (Colloquia Litteraria, 2019)
Onticism of the nation in Cyprian Norwid’s thought The article originates from a larger scale study dealing with the Polish nation and identity in Norwid’s writings. The author exposes the poet’s attention to the philosophy of history and underscores the constant presence of threads linking the Polish affairs with the history of the humankind in Norwid’s poetic and journalistic works. This piece argues that Norwid in his reflection on the nation assumes understanding of the essence of the nation’s being in categories of ethos.